2000
DOI: 10.1097/00005537-200008000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p53/bcl‐2 Co‐expression in Patients With Laryngeal Squamous Cell Carcinoma

Abstract: The co-expression of p53/bcl-2 was an independent predictor of patient outcome and had a prognostic value superior to both parameters considered separately. The rate of apoptosis mainly counterbalanced proliferative activity but appeared not to be significantly influenced by p53, bcl-2, and bax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…In contrast, Hotz et al 35 reported that a high AI in pretreatment tissues was associated with a poor prognosis in advanced head and neck SCC, but their samples did not include maxillary sinus SCC. For other tumors of head and neck such as laryngeal SCC 61 and oropharyngeal SCC, 37 no correlation was found between AI and prognosis. These contradictory findings suggest that the prognostic significance of apoptosis in pretreatment status may vary among tumor sites and/or treatment manners even in head and neck lesions.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Hotz et al 35 reported that a high AI in pretreatment tissues was associated with a poor prognosis in advanced head and neck SCC, but their samples did not include maxillary sinus SCC. For other tumors of head and neck such as laryngeal SCC 61 and oropharyngeal SCC, 37 no correlation was found between AI and prognosis. These contradictory findings suggest that the prognostic significance of apoptosis in pretreatment status may vary among tumor sites and/or treatment manners even in head and neck lesions.…”
Section: Discussionmentioning
confidence: 92%
“…Additional sections providing a surface area of at least 1 cm 2 were stained immunohistochemically (BioGenex, CA, USA) for p53 and bcl-2. Cytoplasmic immunoexpression of bcl-2 and nuclear immunoexpression of p53 were quantified by a SAMBA image analysis system using Immuno A semi-quantitative method, known as histoscore, was also applied to the immunohistochemically stained sections (Staining percentage of cells × staining density [0,1,2,3,4] = Histoscore). 7 Quantitative and semi-quantitative values of p53 and bcl-2 protein expression for each tumour were analysed statistically to identify any correlation with tumour localization, pathological stage of the disease, tumour grade or post-operative survival rate.…”
Section: Methodsmentioning
confidence: 99%
“…Growth arrest in wild-type P53 is dependent on transcriptional activation of P21, which ultimately inhibits cyclin complexes and arrests cells in the G1 to S phase transition (Clarke et al, 1993;Chang et al, 1997;Bouvard et al, 2000). Through the activation of BAX, a proapoptotic gene, and downregulation of BCL-2, an anti-apoptotic gene, P53 plays an essential role in apoptosis (Lane, 1992;Clarke et al, 1993;elDeiry et al, 1994;Silvestrini et al, 1994;Gallo et al, 1999;Sionov and Haupt, 1999;Dijkema et al, 2000;Jackel et al, 2000). It follows that cellular response to radiation may be dependent on a normally functioning P53 gene.…”
Section: P53mentioning
confidence: 99%